Morphology and dynamics of the intertidal floodplain along the Amazon tidal river. Issue 1 (17th January 2019) - Fricke, Aaron T.; Nittrouer, Charles A.; Ogston, Andrea S.; Nowacki, Daniel J.; Asp, Nils E.; Souza Filho, Pedro W. M.
Abstract: Depositional environments along the tidal river downstream of Óbidos have been proposed as important sinks for up to one third of the sediment discharge from the Amazon River. However, the morphology of the intertidal floodplain and the dynamics of sediment exchange along this reach have yet to be described. River‐bank surveys in five regions along the Amazon tidal river reveal a distinct transition in bank morphology between the upper, central and lower reaches of the tidal river. The upper tidal‐river floodplain is defined by prominent natural levees that control the transfer of water and sediment between the mainstem Amazon River and its floodplain. Greater tidal influence in the central tidal river suppresses levee development, and tidal currents increase sediment transport into the distal parts of the floodplain. In the lower tidal river, the floodplain morphology closely resembles marine intertidal environments (e.g. mud flats, salt marshes), with dendritic tidal channels incising elevated vegetated flats. Theory, morphology and geochronology suggest that the dynamics of sediment delivery to the intertidal floodplain of the Amazon tidal river vary along its length due to the relative influence and coupling of fluvial and tidal dynamics. ©  2018 John Wiley & Sons, Ltd. Abstract : River‐bank surveys along the Amazon tidal river reveal a distinct transition in bank and floodplain morphology between the upper, central, and lower reaches of the tidal river. The upper tidal‐river floodplain is most strongly affected by seasonal changes in river stage and closely resembles a purely fluvial system. Tidal energy increases toward the river mouth, disrupting fluvial levee‐building processes in the central tidal river, and dominating sediment transport in the lower tidal river.